Making merchants : the cultural construction of a merchant class in early modern Germany - Howell, Martha C. (Cambridge University Press, 2026)
Using a rare collection of personal narratives written by successful merchants in early modern German-speaking Europe, this study examines how such men understood their role in commerce and in society more generally. As they told it, their honor was based not just on riches won in long-distance trade but, more fundamentally, on their comportment both in and outside the marketplace. As these men described their experiences as husbands and fathers, as civic leaders, as men who "lived nobly," or as practitioners of their faith, they did not, however, seek to obscure their role as merchants. Rather, they built on it to construct a class identity that allowed them entry into the period's moral economy. Martha C. Howell not only disrupts linear histories of capitalism and modernity, she demonstrates how the model of mercantile honor these merchants fashioned would live beyond the early modern centuries, providing later capitalists with a narrative about their own self-worth.
Title from publisher's bibliographic system (viewed on 22 Sep 2025).
Keywords: Merchants -- Germany -- History -- 16th century.; Merchants -- Germany -- History -- 17th century.; Germany -- Commerce -- History -- 16th century.; Germany -- Commerce -- History -- 17th century.